Persepsi Perawat Tentang Evidence Based Nursing Practice (EBNP) di Rumah Sakit - Reni Irmayanti; Hema Malini; Dewi Murni (Jurnal Endurance, 2019)
Evidence-Based Practice is a systematic approach to improving the quality of nursing practiceby collecting the best evidence. The application of Evidence Based Nursing Practice (EBNP) in nursing services has focused on the hospital setting. The concept of EBNP is acceptable but difficult to implement, so it is necessary to study how nurses' perceptions of EBNP are. This study aims to explore nurses' perceptions about EBNP at Bukittinggi Hospital. Qualitative research design with a phenomenological approach. Data collection was carried out through in-depth interviews with six participants using purposive sampling technique. Criteria for inclusion in the sample are the head of the room or the team leader in the nursing service unit. Data were analyzed by the Colaizzi method. The results this research found four themes, (1) Lack of nurses 'understanding of EBNP, (2) Obstacles in EBNP implementation (3) Nurses' expectations in implementing EBNP, (4) Benefits in implementing EBNP. The conclusion this research is the lack of nurses 'understanding of EBNP, there are obstacles in implementing EBNP, nurses' expectations in implementing EBNP and the advantages in implementing EBNP Evidence-Based Practice adalah pendekatan sistematis untuk meningkatkan kualitas praktik keperawatan dengan mengumpulkan bukti terbaik. Penerapan Evidence Based Nursing Practice (EBNP) dalam pelayanan keperawatan telah difokuskan pada tatanan rumah sakit. Konsep EBNP dapat diterima namun sulit dalam implementasinya, sehingga perlu dikaji bagaimana persepsi perawat tentang EBNP. Penelitian ini bertujuan untuk mengeksplorasi persepsi perawat tentang EBNP di RSAM Bukittinggi. Desain penelitian kualitatif dengan pendekatan fenomenologi. Pengumpulan data dilakukan melalui wawancara mendalam kepada enam partisipan dengan teknik purposive sampling. Kriteria inklusi sampel adalah kepala ruangan atau ketua tim pada unit pelayanan keperawatan. Data dianalisis dengan metode Colaizzi. Hasil penelitian ditemukan empat tema yaitu (1) Kurangnya pemahaman perawat tentang EBNP, (2) Hambatan dalam penerapan EBNP (3) Harapan perawat dalam penerapan EBNP, (4) Keuntungan dalam menerapkan EBNP. Kesimpulan penelitian ini yaitu kurangnya pemahaman perawat tentang EBNP, terdapat hambatan dalam penerapan EBNP, harapan perawat dalam penerapan EBNP dan keuntungan dalam menerapkan EBNP